Loving the love of boys: Motives for consuming yaoi media. - Ágnes Zsila; Dru Pagliassotti; Róbert Urbán; Gábor Orosz; Orsolya Király; Zsolt Demetrovics (PLoS ONE, 2018)
In recent years, yaoi has been increasingly popular among youth interested in Japanese media such as anime and manga. Yaoi is defined as commercial and fan-created media that thematically focus on the romantic love between two men, often in a sexually explicit way. Despite the widespread popularity of this Japanese subgenre, there is a lack of empirical studies on the motives for consuming yaoi media that analyze the full range of motives using reliable research methods. The present study aimed to explore and operationalize the motives for yaoi media consumption based on previous qualitative research (Pagliassotti, 2008). Using an online survey, 724 yaoi consumers (58% male; Mage = 30.1 years, SD = 10.4) completed the Yaoi Consumption Motives Questionnaire (YCMQ). According to confirmatory factor analyses, the bi-factor model of nine motives yielded closer fit to the data than the theoretically proposed, first-order ten-factor model and a second-order nine-factor model. The nine-factor YCMQ demonstrated strong psychometric properties in terms of factor structure, internal consistency, and measurement invariance. These results indicate that the 31-item YCMQ is an appropriate instrument to assess individuals' motives for consuming yaoi media.